2016
DOI: 10.1007/s10103-016-2100-y
|View full text |Cite
|
Sign up to set email alerts
|

Three consecutive days of application of LED therapy is necessary to inhibit experimentally induced root resorption in rats: a microtomographic study

Abstract: Previous studies have suggested that phototherapy may modulate orthodontic tooth movement and the incidence of root resorption. We aimed to identify a minimal dose-response relationship to LED therapy with regard to orthodontic tooth movement (OTM) and root resorption in rats. Forty-eight male Wistar rats were divided into six groups with equal and random distribution: control (C) no intervention; three daily LED irradiation (CLED); submitted only to OTM (RR); OTM and LED irradiation on the first day (LED1); O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Similar force has been used previously in laser studies and induced tooth movement (16)(17)(18). Due to the small intraoral space in rats, we performed the irradiation on the facial skin area (adjacent to the upper molars) to accommodate the probe of the LED instrument (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Similar force has been used previously in laser studies and induced tooth movement (16)(17)(18). Due to the small intraoral space in rats, we performed the irradiation on the facial skin area (adjacent to the upper molars) to accommodate the probe of the LED instrument (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, irradiation should be applied during the initial phase of the acute inflammatory response and during the recruitment and differentiation of osteoclasts. 19 Considering the amount of tooth movement in all groups, less OTM was detected under LED and laser irradiation in relation to the control. When both irradiated groups were compared, no significant differences were detected between them.…”
Section: Discussionmentioning
confidence: 86%
“…25 Therefore, some studies have confirmed the acceleration of tooth movement stimulated by laser therapy, 18,20,23,26 and other studies have showed reduced resorption in relation to root resorption. 19,24,27 The root resorption areas on the mesial surface of the distal palatal root in both the laser and LED groups presented similar effects, although the specimens from the LG exhibited slightly more resorption area than that of the DG. However, while the extent of resorption area varied in each group, extensive lacunae were observed mostly in the LG.…”
Section: Discussionmentioning
confidence: 90%
“…This process results in beneficial therapeutic outcomes including but not limited to the alleviation of pain or inflammation, immunomodulation, and promotion of wound healing and tissue regeneration.^ [1]. PBM therapy was found to have multiple clinical benefits, which includes reducing pain [2][3][4][5][6][7], improving wound healing [8][9][10][11], accelerating bone healing [12][13][14][15][16][17], promoting osteointegration [18], facilitating orthodontic tooth movement [19][20][21][22][23][24][25][26], stimulating bone formation [27][28][29][30][31], and improving periodontal tissue repair and decreasing inflammation and root resorption [23,26,32]. The light sources were laser or a light-emitting diode (LED).…”
Section: Introductionmentioning
confidence: 99%